Epidendrum choccei (Orchidaceae), a new species from Northern Peru - Acuña-Tarazona, Margoth; Hagsater, Eric; Ayala, Elizabeth Santiago (Phytotaxa, 2019)
Epidendrum choccei, new species of Orchidaceae, from Northern Peru is here described, illustrated and compared with most similar species.